Manajemen kelas siswa SMK bidang keahlian tata busana di SMK Negeri 6 Yogyakarta - Jumariah Jumariah; Supriyoko Supriyoko (Universitas Sarjanawiyata Tamansiswa, 2016)
This research was conducted with the aim to (1) describe the class management expertise in the field of fashion, especially with respect to educational facilities and infrastructure management, educational materials and teaching staff at SMK 6 Yogyakarta, (2) Describe the student work readiness skills program in fashion SMK N 6 Yogyakarta. This research is a case study using a qualitative approach. The location of this research will be carried out in school SMK Negeri 6 Yogyakarta. In the process of data collection, the researcher as the key instrument that directly goes into the field (class) through observation, interview, and documentation. Data analysis that carried out in this study is a model Interaktive Analysis of Miles and Huberman. Based on the results of research conducted, it can be concluded, that (1) Class management at SMK N 6 Yogyakarta in conducting education in the field of fashion expertise can be considered good. It can be seen from the aspect of education facilities and infrastructure management, educational materials and teaching staff. (2) the student’s readiness to work at SMK N 6 Yogyakarta can be considered good. It can be seen from (a) the readiness of students in the field of education or professional, (b) student readiness and cooperation in the social field or relationships with others, and (c) the readiness of students in the field of psychological and personality or attitude. The readiness of the students’ work can be considered as a form of success of SMK N 6 Yogyakarta in conducting effective classroom management, according to the orientation of vocational education.